DAMPAK PANDEMI COVID-19 TERHADAP SOSIAL EKONOMI MASYARAKAT ACEH (STUDI KASUS DI DESA LHANG) - Marlinda, Leni; Akhyar, Akhyar; Hasanah, Hasanah; Saifuddin, Saifuddin; Zaki, Ammar (Jurnal Dedikasi Pendidikan, 2025)
The emergence of the corona virus or covid-19 is known to have originated from wuhan, China. The virus has spread from physical contact to all over the world, including Indonesia. Most of the activities of people in an area, especially Aceh, have been hamered and forced to stop. All policies are implemented by the government to prevent and reduce the spread of covid-19. In addition to affecting human health, this also has an impact on the socio-economic life of the people in Aceh. Your research uses a qualitative descriptive method to understand the socio-economic situation of the community in depth and uses a descriptive approach to get a general picture of the community. Data connection techniques in this study use observation, interview and documentation techniques. The results of the research conducted in this study are the impact of the covid-19 pappndepmipc has caused changes in various aspects of human life to be disrupted, decreasing social relations between communities to causing changes in economic income which is increasingly decreasing